Cystic Fibrosis in Malaysian Children - Norzila, M.Z.; Norrashidah, A.W.; Rusanida, A.; Chan, P.W.K.; Azizi, B.H.O. (http://myais.fsktm.um.edu.my/5688/, 2005)
Cystic fibrosis (CF) is an autosomal recessive disease commonly found among the Caucasian population. The availability of sweat test and with increasing experience have made it possible to diagnose more cases of CF. Our first case of CF was diagnosed 16 vears ago and to date we have managed sixteen cases of CF. Sixteen children were diagnosed with CF in our units at the Paediatric Institute and University Malaya Medical Centre (UMMC). They were referred with either one or all of the following symptoms: i) recurrent pneumonia, ii) bronchiectasis, iii) failure to thrive, iv) malabsorption or v) history of meconium ileus obstruction during the neonatal period. When the clinical features suggested strongly of CF sweat tests will be performed in duplicates and considered positive when the sweat chloride or sweat sodium was more than 60 mmol/l for both results. Seventy- two hours fecal fat excretion or stool for fat globule was performed to document malabsorption. From the year 1987 to 2003, 16 patients were confirmed to have cystic fibrosis in Malaysia by positive sweat tests. Thirteen patients were diagnosed in Paediatric Institute while the remaining three were diagnosed in UMMC. On follow-up two patients died due to severe bronchopneumonia at the age of two years old. Although once considered rare, CF should now he considered in any children with clinical presentations of recurrent chest infections, bronchiectasis, in the presence or absence of malabsoption simptoms and in neonates with rneconium ileus obstruction.